Technology Adoption Readiness as A Mediating Mechanism Between Omnichannel Strategy, Digital Competence and MSME Marketing Performance in Indonesia - Siska Ernawati Fatimah; Ratih Hurriyati; Soesanty Maulany (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The rapid development of digital technology has significantly transformed consumer purchasing behavior. Customers increasingly expect seamless experiences across both online and offline channels, creating new challenges for micro, small, and medium sized enterprises (MSMEs) in managing integrated marketing systems. In this context, MSMEs' ability to adopt and use digital technologies becomes an important factor in improving marketing performance. Purpose: This study examines the role of technology adoption readiness as a mediating mechanism between omnichannel strategy, digital competence, and MSME marketing performance in Indonesia.Design/methodology/approach: A quantitative research approach was employed using survey data collected from 180 MSME owners in Cirebon City, West Java, Indonesia, who operate at least two marketing channels. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to evaluate both the measurement model and the structural relationship among variables.Findings/Results: Results indicate that omnichannel strategy and digital competence significantly enhance technology adoption readiness. Furthermore, technology adoption readiness has a significant positive effect on marketing performance. The structural model explains 88.3% of the variance in marketing performance (R²=0.883), indicating strong predictive capability. The mediation analysis shows that technology adoption readiness fully mediates the relationship between omnichannel strategy, digital competence, and marketing performance.Conclusion: These findings suggest that MSME marketing performance can be improved not only through channel integration and digital skills but also through strong technological readiness that supports digital transformation.Originality/value (State of the art): This study contributes to the Technology Organization Environment (TOE) framework by highlighting the mediating role of technology adoption readiness in linking strategic orientation and digital capability to marketing performance in the MSME context.  Keywords:  technology adoption readiness, omnichannel strategy, digital competence, MSMEs, marketing performance